Adult degenerative scoliosis associated with increased aortic diameter and plaque burden and composition. (June 2016) - Ayça, Burak; Rakıcı, Taşkın; Atıcı, Yunus; Avsar, Murat; Yuksel, Yasin; Akın, Fatih; Okuyan, Ertugrul; Hakan Dinckal, M
Objective: In this study, we aimed to investigate the relationship between adult degenerative scoliosis (ADS) and the aortic plaques and diameters. Method: We included 219 patients with ADS and 100 control patients without ADS. Diameters of ascending, arch, descending and abdominal aorta and number, localization and types of the aortic plaques, and the Cobb angles of all patients were measured from computed tomography (CT) images. We divided the patients with ADS into three groups according to the Cobb angle, and divided them into four groups according to level of spine deformity. Results: The patients with ADS had a larger aorta and more aortic plaques (both, p  < 0.001). The patients with ADS had more fibro-fatty and mix plaques (both, p  < 0.001). The patients with severe ADS had larger diameters of the ascending and arch of the aorta ( p  = 0.026 and p  = 0.027, respectively). The patients with the main thoracic curve had a larger ascending aorta and the patients with a thoracolumbar curve had more aortic plaques ( p  = 0.035 and p  = 0.029, respectively). In multivariate regression analysis, the ADS was an independent risk factor for both aortic dilatation (>3.6 cm) and aortic plaque build-up (both, p  < 0.001). Conclusion: The ADS may be a risk factor for aortic dilatation and aortic atherosclerosis.